In situ ruminal digestion kinetics of different forages in buffalo calves - Sarwar, M; Rasool, Sahid; Nisa, Mahr-Un; Sial, M A (The Indian Journal of Animal Sciences, 2012)
Dry matter (DM) and neutral detergent fibre (NDF) digestabilities and rate and extent of legumes, viz, berseem (Trifolium alexandrinum), lucerne (Medicago sativa), cowpea (Vigna sinensis) and nonÂ· legumes such as maize (Zea mays), millet (Pallicum miliaceum), sorghum (Sorghum vulgare) in ruminally fistulated male buffalo calves were determined. Nylon bags measuring 13 cm x 21 cm, with an average pore size of 50 mm, were used. Sample (10 g) was weighed into each bag and exposed to the ruminal fermentation for 0, 1, 2, 6, 10, 16, 24, 36, 48 and 96 hr. DM and NDF degradability was measured at 48 hr. Extent of DM and NDF disappearance was determined at each time point. Rates of disappearance of DM and NDF were determined by regressing the natural logarithm of the percentage of original DM and NDF remaining in the bags between 1 and 96 hr. Dry matter digestibility (DMD) of the legume forages when incubated in the rumen of male buffalo calves was greater (p< 0.05) than that of grasses. Extent of digestion followed similar pattern as DMD. Rate of DMD was higher in legumes than grasses. The NDF degradability (NDFD) of legumes and grasses did not differ. The legumes had higher (P< 0.05) rates and lower extents of NDF digestion compared to grasses.